BACTERIOCINS OF FACULTATIVELY-ANAEROBIC ENDOSPOREFORMING BACTERIA - М. В. Штеніков; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2017)
The survey provides information on low-weight proteins of endosporeforming facultative anaerobic bacteria (EFAB) – bacteriocins that have antimicrobial activity, their classification, structure and properties. The bacteriocins of EFAB are divided into that, which undergoes secondary modification during the synthesis, and such that do not. First, in its turn, they are divided into lantibiotics, cyclic peptides, sactibiotics, glicocins, linear azole-containing and lasso bacteriocins, the last are found in EFAB still only with bioinformatics methods. Among nonmodified bacteriocins of EFAB there are separated pediocin-like and unclassified ones. A separate group is represented by heavy bacteriocins that have a high molecular weight, and are currently poorly understood. Knowledge of different taxonomic groups in terms bacteriocinogenity EFAB is very uneven currently. General producers are belonging to the genera Bacillus and Paenibacillus, for some families there is no information in the literature at all. Investigation of EFABbacteriocins is a promising direction both in fundamental and applied research.